NEW DATA ON THE CATAGENIC TRANSFORMATION OF ORGANIC MATTER IN THE BASAL HORIZONS OF THE SEDIMENTARY COVER IN THE NORTHERN PARTS OF THE WEST SIBERIAN PLATFORM - Yermakov V.I.; Skorobogatov V.A. (My University, 1990)
In determining the oil and gas potential of the sedimentary cover on the West Siberian platform (WSP), it is important to know the full range of catagenesis of organic matter (OM) in the sections in different areas and regions. This applies above all to its relatively little studied northern areas. This paper attempts for the first time to synthesize the data on the catagenesis of OM in the basal horizons of the sedimentary cover in the northern regions of the WSP on the basis of our own collection of coals and coal inclusions from the Tyumen formation (620 individual determinations of the RIV2, including 105 from the middle and lower to basal horizons of the Jurassic).
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская